Penerapan Konseling Kelompok untuk Meningkatkan Minat Membaca Siswa Kelas VIII SMP Negeri 12 Kota Kupang - Naluk, Lusia Maria Ariesta; Lohmay, Imanuel; Nalle, Andriani Paulin; Saba, Khetye R. (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2023)
The purpose of this study was to determine the effect of applying group counseling to increase students' interest in reading. This research is a quantitative approach. The method used is quasi-experimental. This research was conducted at SMPN 12 Kota Kupang with a period of ± 3 months. The population of this study was 160 people using the purposive sampling technique, so that a total sample of 5 people was obtained. The results of this study obtained a score of 1 person with a score of 72 and 4 others with a score of 70 which are in the active category. Based on the calculation results, it was found that 5 students were very active in the group counseling process. All students involved are in the active category with a score range of 60-73. There is an influence of the application of group counseling to increase students' reading interest in class VIII SMP Negeri 12 Kota Kupang where the posttest score is higher than the pretest score. This means that the group counseling process can increase students' interest in reading.